Priority directions of development of tourist services of Ukraine - Oveskov, O. V. (ТДАТУ, 2020)
One of the main external factors hindering the development of tourism in Ukraine is the unfavorable conditions for entrepreneurship in general and tourism in particular, the imperfection and obsolescence of infrastructure. Ukraine has all the objective prerequisites to become one of the leading tourism countries in the world, but the analysis of the current state of the domestic tourism and recreation industry indicates the low efficiency of this industry today.
Keywords: tourism; COVID-19; development of tourism in Ukraine